Synthesis and Structural Characterisation of Hafnium(IV) Mono‐ and Diphthalocyanines Obtained under Oxidation Conditions with Halogens. Issue 32 (19th September 2013) - Janczak, Jan; Kubiak, Ryszard
Abstract: New sandwich‐type hafnium(IV) diphthalocyaninato and hafnium(IV) monophthalocyaninato complexes were obtained in crystalline form under oxidation conditions with halogens. Partially oxidised by iodine, a sandwich‐type hafnium(IV) diphthalocyaninato complex with a composition of HfPc2 I2 (Pc 2– = phthalocyaninate) crystallizes in two crystalline modifications1 and2, depending on the thermal conditions. Both modifications are tetragonal and differ in the disordering model. Statistically, in both modifications, in two of three [HfPc2 ] sandwich units the closed‐shell d 0 Hf 4+ cation is sandwiched by a phthalocyaninato ligand (Pc 2– ) and a one‐electron‐oxidised Pc –· π‐radical ligand. The π‐radical character of the Pc –· ligand was detected by EPR spectroscopy. In1, the Hf 4+ and the symmetrical triiodide ions, which were detected by resonance Raman spectroscopy, are disordered in the crystal. However, in crystal2, only the symmetrical I3 – anions are disordered, but the Hf 4+ cations are ordered. The hafnium(IV) monophthalocyanines with the composition of HfPcI2 Pht (3 ) and HfPcBr2 Pht (4 ) (Pht = phthalonitrile) are isostructural. The seven‐coordinate Hf 4+ cation is surrounded by four isoindole N atoms of a Pc 2– macrocycle, two halides (I – or Br – ), and by a N atom of one of the two cyano groups of phthalonitrile. The last compound with a composition of HfPcCl2 (5 ) exists as a doubly bridged dimeric complex, bis[(μ2 ‐chlorido)chlorido(phthalocyaninato) hafnium(IV)], in which the coordination number seven of Hf 4+ cations is achieved by four isoindole N atoms of Pc 2–, two bridging, and one terminal Cl – ligand. The π–π interactions between the Pc macrocycles in the sandwich system [HfPc2 ] have an influence on the HOMO–LUMO transition, compared with the hafnium(IV) monophthalocyanines, and result in a blueshift of approximately 20 nm compared to that observed for hafnium(IV) monophthalocyanines. Abstract : The direct reaction of pure hafnium with phthalonitrile under oxidation conditions with halogens yields different types of hafnium(IV) phthalocyaninato (HfPc) complexes in crystalline form. Single‐crystal X‐ray diffraction analysis, resonance Raman and UV/Vis spectroscopy, and magnetic methods were used to characterize the HfPcs.